Protect-me: a parallel-group, triple blinded, placebo-controlled randomised clinical trial protocol assessing antenatal maternal melatonin supplementation for fetal neuroprotection in early-onset fetal growth restriction - Palmer, Kirsten R; Mockler, Joanne C; Davies-Tuck, Miranda L; Miller, Suzanne L; Goergen, Stacy K; Fahey, Michael C; Anderson, Peter J; Groom, Katie M; Wallace, Euan M (BMJ open, 2019)
IntroductionFetal growth restriction (FGR) is a serious pregnancy complication, associated with increased rates of perinatal death and morbidity among survivors. Most commonly FGR results from placental insufficiency, where the placenta fails to deliver the oxygen and nutrients required for normal fetal growth. This leads to fetal oxidative stress, resulting in organ damage through lipid peroxidation. The early developing brain is particularly susceptible, such that FGR is associated with poorer neurodevelopment, witnessed as cognitive and behavioural dysfunction, and cerebral palsy. Promisingly, melatonin, a lipid soluble antioxidant is neuroprotective in animal models of FGR. We present a protocol outlining a randomised, placebo-controlled trial to explore whether antenatal maternal melatonin supplementation in pregnancies with severe, early-onset FGR can improve neurodevelopment among survivors at 2 years of age.Methods and analysesWe will recruit 336 women with a singleton pregnancy complicated by FGR between 23+0 and 31+6 weeks gestation. Participants will be randomised, stratified by gestational age, to either 30 mg melatonin per day or a visually identical placebo, continued until birth. Measures of maternal and fetal health will be collected until birth. Timing of birth will be determined by the treating clinical team in discussion with the woman. Neonatal and infant neurodevelopmental assessments will be undertaken, consisting of brain MRI at term corrected age, general movements assessment at term and 3 months’ corrected age, and Bayley Scales of Infant & Toddler Development-III and Infant Toddler Social Emotional Assessment at 2.5 years corrected age. Analyses will be on intention to treat. The primary outcome is a difference of 5 points in the cognitive domain of the Bayley-III. Secondary outcomes address maternal and fetal safety.Ethics and disseminationThis trial has Monash Health Human Research and Ethics committee approval (17-0000-583A). Findings will be disseminated through peer-reviewed publications, conference presentations and to participants.Trial registration numberACTRN12617001515381; Pre-results